From Filter Paper to Functional Actuator by Poly(Ionic Liquid)‐Modified Graphene Oxide. Issue 12 (16th March 2016) - Song, Haojie; Lin, Huijuan; Antonietti, Markus; Yuan, Jiayin
Abstract : A commercially available membrane filter paper composed of mixed cellulose esters bearing typically an interconnected pore structure is transformed into a stimuli‐responsive bilayer actuator by depositing a thin film of poly(ionic liquid)‐modified graphene oxide sheets (GO‐PIL) onto the filter paper. In acetone vapor, the as‐synthesized bilayer actuator bends readily into multiple loops at a fast speed with the GO‐PIL top film inward. Upon pulling back into air, the actuator recovers its original shape. The asymmetric swelling of the top GO‐PIL film and the bottom porous filter paper toward organic vapor offers a favorably synergetic function to drive the actuation. The PIL polymer chains in the hybrid film are proven crucial to enhance the adhesion strength between the GO sheets and the adjacent filter paper to avoid interfacial delamination and thus improve force transfer. The overall construction allows a prolonged lifetime of the bilayer actuator under constant operation, especially when compared to that of the GO/filter paper bilayer actuator without PIL. Abstract : A porous bilayer membrane actuator is fabricated from a porous filter paper deposited with a thin film of poly(ionic liquid)‐modified graphene oxide nanosheets (GO‐PIL). Due to the asymmetric swelling of the top GO‐PIL film and the bottom porous filter paper toward organic vapor, the bilayer membrane shows rapid, reversible bending with the top GO‐PIL dense film inward.